Morfologia e granulometria de uma praia de macro-maré: o caso de Fortalezinha – ilha de Maiandeua (Nordeste do Pará) - RAIOL, Kleper de Lima (2019)
The coastal zone is a region of great social, economic and environmental analysis of data for that region to confirm, regarding to that, if the area is acquiring erosive or progradational trend. Thus, this work aims to analyze the influence of the amazon seasonality in morphodynamics configuration in the Fortalezinha beach, located on the island of Algodoal / Maiandeua, Maracanã County, State of Pará. The region is influenced by a wide range of rain (annual average of 2800 milimeters) and dominated by semidiurnal macrotidal (average height of 4-6 meters) and the interaction of the trade winds with a northeast direction, as the main generator of waves. Each profile is 850 meters away from each other, following till the coast of the beach. The samples were collected during the season with a very low range of rain (October 17 - 10/18/2012) and also during the period that the rain is more frequent (March 14 - 03/15/2013). All samples were collected in the spring tide period. It was noted that due to seasonality between the dry and rainy seasons, there is a difference both in the preferred direction of the winds, height and period of the waves, where all these environmental factors have had a huge influence to the beach to get a positive sediment budget. The synergy between these agents have changed the morphodynamics of the area, from a intermediate type of beach to a dissipative type, on Fortalezinha beach.